Mahkota for Muslimah is a hijab / Nurul Hajar Shaharuddin, Ridzwana Macrob and Wan Nurul Diana Wan Mahmood - Shaharuddin, Nurul Hajar; Macrob, Ridzwana; Wan Mahmood, Wan Nurul Diana (2013)
Mahkota is established by three shareholders who are having experience and skills in each position. For instance, as a General Manager, she had experience in managing some small group and has the skill and knowledge of leadership and etc. Mahkota is a new business in an entrepreneurship field, so we didn't have enough budget to hire more staff for some of the positions in the company. Then, we decide to be responsible for two positions per person. For example, instead of being a General Manager, she also responsible as an Administrative Manager. On the other hand, the Marketing Manager is also responsible for the financial as a Financial Manager. Mahkota is mainly creating their own product on veils and market the product to the customer either directly or through online services provided. We have chosen Tesco Seri Alam as our business location as it has a large population of peoples and it motivates us to attract them to buy our product. We have- identified our product's demand and it has a quite high demand during Eidul Fitri season. In order. to ensure the business run smoothly, we had made sure that we are capable of the position given. We are together will cooperate to ensure that Mahkota will gain and" attain maximum profit even we are using fewer resources. We are trying our best to run this business and we believe that our busyness would not disappoint us as we. the belief that each of our success and failure is depends-on our effort. We are going to overcome all the obstacles and 'challenges in order to pursue our vision and mission of the business. On the Other hand, we will always give an effort to improve our services and come out with the latest design.